2014
DOI: 10.4236/health.2014.62025
|View full text |Cite
|
Sign up to set email alerts
|

Misuse of prophylactic antibiotics and prevalence of postoperative wound infection in obstetrics and gynecology department in a Sudanese hospital

Abstract: Purpose: This study was conducted to audit prophylactic antibiotic use and to quantify the rate of wound infection. Methods: Across-sectional prospective study was conducted in the Obstetrics and Gynecology Department in Khartoum Teaching Hospital, Sudan during March 1st to 31st October 2010. All Patients (aged >18 years) were included. Results: Overall 725 patients were included. The performed surgical procedures were 751; of these 578 (76.9%) were Caesarean sections. Overall rate of wound infection was 7.8%.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 21 publications
2
11
1
Order By: Relevance
“…A single dose is generally considered sufficient and its effectiveness compared with prolonged post-operative antibiotic use has been proven in several studies in Africa [26]. However, post-operative antibiotic overuse in other African countries has been described [18,27]. The findings of this study were similar to those previously reported: antibiotic overuse was seen even among low-risk patients such as those without SIRS/HAI and those with class 1 wounds.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A single dose is generally considered sufficient and its effectiveness compared with prolonged post-operative antibiotic use has been proven in several studies in Africa [26]. However, post-operative antibiotic overuse in other African countries has been described [18,27]. The findings of this study were similar to those previously reported: antibiotic overuse was seen even among low-risk patients such as those without SIRS/HAI and those with class 1 wounds.…”
Section: Discussionsupporting
confidence: 85%
“…Surgical antibiotic prophylaxis and AMR interact closely with each other: declining efficacy of SAP because of AMR could jeopardize safe surgical procedures whereas inappropriate, prolonged SAP could select for resistant microorganisms [16,17]. A study in Sudan showed that SAP was often given inappropriately: all those who received SAP had extended antibiotic use, with an average of eight days whether they developed SSI or not [18]. However, such epidemiologic evidence of inappropriate antibiotic use related to SAP in LMICs is underreported in the literature.…”
mentioning
confidence: 99%
“…As part of the irrational use of antibiotics, a study was done in Sudan by (Elbur A et al, 2014) regarding the use of antibiotics as a surgical prophylaxis in obstetrics and gynecology wards given the high rates of surgical site infections. This study revealed 98.8% of admitted cases received antibiotics pre-operatively while 100.0% received antibiotics post-operatively for an average duration of 8 days.…”
Section: Irrational Use Of Antibiotics As a Prophylaxis In The Irratimentioning
confidence: 99%
“…Surgical site infections are also a leading concern to which the effectiveness of prophylactic antibiotics has been established (8). However, the growing use of prophylactic surgical antibiotics has been associated with resistance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation